(untitled) (Texas Journal of Medical Science, 2024)
In this article, the role of international folk medicine and the analysis of research conducted in this field, as well as the results of practical work, methods of folk medicine that have been proven to be effective and safe, and the need to harmonize traditional medicine with modern medicine were highlighted